Superpuppy how to choose, raise and train the best possible dog for you - Pinkwater, Jill; Pinkwater, Daniel Manus 1941- (Seabury Press, 1977)
A guide to buying, training, and caring for a dog, with special emphasis on understanding its personality, feelings, and reactions to new situations.